2013
DOI: 10.5812/ircmj.7990
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Additional Pleural Procedures onto Recurrence Rates on the Spontaneous Pneumothorax Surgery

Abstract: BackgroundSpontaneous pneumothoraxes constituted 1/1000 hospital admissions. They are particularly one of life threatening health issues in combination with bilateral pneumothorax, tension pneumothorax, repertory failure or COPD.ObjectivesThe cases of spontaneous pneumothorax represent a significant portion of the patients profile within the chest surgery clinics. The risk of recurrent pneumothorax in post thoracoscopy is between 2% and 14%, thus the subject of cure treatment and approach is still controversia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
1
4
0
3
Order By: Relevance
“…[1314] However, a few studies have demonstrated that PSP recurrence rate is higher after VATS than after open thoracotomy. [1516] Further, in agreement with the findings of this study, adding pleurodesis to the surgical exploration has been shown to be ineffective in decreasing the recurrence rate of PSP. [1317]…”
Section: Discussionsupporting
confidence: 85%
“…[1314] However, a few studies have demonstrated that PSP recurrence rate is higher after VATS than after open thoracotomy. [1516] Further, in agreement with the findings of this study, adding pleurodesis to the surgical exploration has been shown to be ineffective in decreasing the recurrence rate of PSP. [1317]…”
Section: Discussionsupporting
confidence: 85%
“…2a). There was no significant difference in the duration of tube thoracostomy between patients with combined interstitial pneumonia with emphysema (13 [4][5][6][7][8][9][10][11][12][13][14][15][16][17] days) and without emphysema (15 days) (Fig. 2b).…”
Section: Treatment Of Pneumothoraxmentioning
confidence: 99%
“…[5][6][7][8] Approximately 60%-80% of secondary spontaneous pneumothorax cases are related to COPD or pulmonary emphysema in Japan, although the prevalence of COPD/emphysema as the cause of pneumothorax varies between countries. [5][6][7][8][9][10] Other causes of secondary spontaneous pneumothorax include interstitial lung diseases such as idiopathic pulmonary fibrosis, infectious diseases such as tuberculosis and pneumonia, and primary/metastatic lung cancers. Interstitial lung diseases account for 5%-15% of the cases of secondary spontaneous pneumothorax in Japan, [7][8][9] and the combination of pulmonary fibrosis and emphysema further heightens the risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20) Only one recurrence of pneumothorax (3.85%) was found in the VATS group, which was consistent with a frequency of 2%–14% in previous studies. 24) Lung collapse during the operation and expansion following the operation caused by VATS, combined with tension of sutures, may explain the postoperative recurrence of pneumothorax. 25) The VATS group underwent pulmonary bullae resection combined with pleural abrasion.…”
Section: Discussionmentioning
confidence: 99%